The Arab Tendency in the Thought of the Algerian Elite at the Beginning of the Twentieth Century AD - Chatra, Khireddine (Al-Adab Journal, 2023)
Many Algerian writers and literary figures have been calling on Arab peoples and directing their youth to absorb from the depths of the Arab-Islamic civilization. In so doing, they enriched the Arabic library with a rich literary and poetic heritage, which is a significant addition of creativity that has enriched and developed the Arab-Islamic dimension. What I seek to illustrate in this research study is an analysis of the motives inherent in the Algerian personality that have led its elites to crystalize and reformulate a national consciousness and propensity for Arabism and Islam, not only in Algeria but also in the Arab world as a whole. And, also, to search for a set of answers related to some fundamental questions in this subject, including: What is the relationship of Algerian personality and national awareness in the modern era? What are the factors of spreading national awareness among the Algerian elites? What are the manifestations of the Algerian contribution to the Arab national thought, and how to deal with the dilemma of Arab identity struggle among the Algerian elites?